Une gestion plurielle des illégalismes : négociations et contradictions dans la régulation des eaux usées au Maroc - Pierre-Louis Mayaux; Naïma Fezza; Zhour Bouzidi (L’Année du Maghreb)
Foucaldian studies on the management of popular illegalisms tend to focus on their differential treatment by the State according to the social groups concerned. In doing so, they have been less interested in the everyday power relations, negotiations and compromises within the state that shape the regulation of illegal practices. In the case of Morocco, this article thus looks at the plural management of illegalisms -rather than their differential one- as it emerges from the interactions between a variety of public agencies concerned with the same set of extra-legal practices, and which have different positions regarding them. It does so by studying the use of untreated, and therefore highly contaminated, wastewater for small-scale market gardening in the heart of the city of Meknes.The management of these illicit water uses primarily involves local agents of the Ministry of the Interior (the moqqadems) as well as their hierarchy (qaïds, General Directorate of Local Authorities in Rabat). But it also includes other public agencies, such as the water company (RADEM), the Sebou river basin agency (ABHS) which issues water use permits, and the city of Meknès. How, then, do all these organizations interact in the management of these illegalities, and with what effects ?The fieldwork reveals that the management of illegalisms is fraught with tensions and contradictions between different segments of the state. These tensions lead to unstable compromises and frequent shifts between forbearance, negotiation and coercion. Thus, the moqqadems are structurally inclined to forbearance because of two main factors : their daily confrontation with users’ capacities of resistance, which dissuades them from repressing too harshly ; and their homology of subaltern position with the latter, which makes them sensitive to the moral economy of subsistence that animates the farmers. However, this posture of indulgence only heightens tensions with other State actors. This is particularly the case with the water company, RADEM, which sees some of its wastewater being intercepted before reaching the treatment plant, which threatens its proper functioning. RADEM officials lament the tolerance shown by the moqqadems, while also criticizing the inaction of the ABHS despite its legal mandate to verify, in collaboration with the Ministry of the Interior, the legality of water withdrawals. The municipality of Meknes is also trying to put an end to farming practices, which run counter to its strategy of setting up a “green” and recreational space in the area. These various pressures lead the moqqadems to forge shifting and uncertain compromises with the farmers, marked in particular by an attempt to invisibilize their practices in the public space. Thus, and contrary to what the literature on state indulgences generally demonstrates, the regulation of illicit practices in no way guarantees a minimally satisfactory political exchange between the rulers and the ruled. Rather, frustrations abound on both sides. Many State actors would like to see much stronger sanctions, while the moqqadems are constantly exposed to contradictory pressures, including calls for coercion, farmers' capacity to resist and adapt, and the recognition of their moral right to subsistence. As for the farmers, the perpetuation of their illicit practices does not open up any prospect of genuine development, but rather epitomizes a situation of deadlock and lack of alternative. As elsewhere, the illegal condition is experienced as a form of "degraded citizenship" : it constitutes a complex, precarious and constantly shifting combination of legality and illegality.Broadening the analysis so as to include all state actors involved in the management of illegality thus makes it possible not to presume the functionality of this management for the reproduction of the social order. The plural and often contradictory regulation of illegalisms does not necessarily nurture the gratitude and political loyalty of the public concerned. It reveals as much the precarity and instability of the compromises between the state and its subaltern populations, and the frustrations that these compromises engender.